Holeboard maze-learning deficits and brain monoaminergic neurotransmitter concentrations in rats after intracerebroventricular injection of 3-bromopyruvate - Frölich, Lutz; Ding, Andreas; Hoyer, Siegfried (Pharmacology, biochemistry and behavior, 1995)
3-Bromopyruvate is a suicide inhibitor of pyruvate dehydrogenase complex in brain homogenates, and after intracerebral injection reduces acetylcholine tissue content and muscarinic cholinergic receptors in brain cortex and hippocampus for extended periods of time. A stereotaxic injection of 0.2 μmol 3-bromopyruvate was given twice into the cerebral ventricles of male Wistar rats. Ten weeks later, the animals were tested for learning deficits in a food-motivated complex holeboard test. 3-Bromopyruvate-treated rats showed an increased number of visits to nonfood-baited holes over a 5-day testing period (four trials per day) compared to sham-operated control rats, an increased number of visits to food-baited holes over the first 2 days of the testing period and an increased time for completing the task. There were no changes in brain monoaminergic neurotransmitter concentrations compared to controls. The results indicate that long-term learning deficits in a spatial discrimination paradigm are caused by 3-bromopyruvate, which might be related to a cholinergic deficit induced by a primary inhibition of brain glucose metabolism at the step of pyruvate dehydrogenase complex. This animal model may be useful for behavioral studies in relation to neurodegenerative diseases like dementia of Alzheimer type.